Assessment of sex differences in ventricular-vascular coupling of left ventricular and aortic flow derived from 4D flow MRI in healthy, young adults. (5th March 2021) - Pewowaruk, Ryan; Rutkowski, David; Johnson, Cody; Wolfinger, Amanda; Roldán-Alzate, Alejandro
Abstract: To gain further insight into male–female differences in cardiovascular conditions it is important to understand sex differences in healthy populations. A previous study from our group of 39 healthy young volunteers (20–35 years) paradoxically found that men had greater left ventricular (LV) kinetic energy (KE) but women had greater LV vorticity. We reanalyzed cardiac four-dimensional flow MRI data from 20 of the original subjects (10 male and 10 female) to quantify aortic flow in addition to LV flow. The combination of LV and aortic flow parameters were then used to calculate ventricular vascular coupling of KE and vorticity. The sex difference found in LV flow were not found in aortic flow and the ventricular-vascular coupling of LV-to-aortic flow was similar between men and women. Dimensional analysis to account for differences in cardiac output and ventricular volume explained the differences found in LV flow. The analysis methods and results of this study may be of further use in understanding ventricular vascular coupling of transported flow variables in healthy sex differences, healthy aging, and various cardiovascular conditions.